2017
DOI: 10.1038/s41598-017-13958-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular consequences of myocardial bridging: A meta-analysis and meta-regression

Abstract: Myocardial bridging, a congenital abnormality in which a coronary artery tunnels through the myocardial fibres was usually considered a benign condition. Many studies suggested a potential hemodynamic significance of myocardial bridging and some, usually case reports, implied a possible correlation between it and various cardiovascular pathologies like acute myocardial infarction, ventricular rupture, life-threatening arrhythmias, hypertrophic cardiomyopathy, apical ballooning syndrome or sudden death. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 99 publications
0
38
0
4
Order By: Relevance
“…The authors concluded that autopsy studies are the gold standard in evaluating the prevalence of MB and that high-resolution CT scanning of coronary arteries should be preferred over coronary angiography studies. It has usually been considered as a benign condition but there are studies suggesting a potential haemodynamic significance of MB and some, usually case reports, indicates a possible association between MB and various cardiac pathologies like AMI, left ventricular rupture, life-threatening arrhythmias, hypertrophic cardiomyopathy, apical ballooning syndrome or sudden death 38 . MB is suggested to be a possible underlying mechanism for MINOCA but a subset of the SMINC-study showed similar prevalence for MB in MINOCA, with or without takotsubo syndrome (TS), as in healthy controls 39 .…”
Section: Myocardial Bridgingmentioning
confidence: 99%
“…The authors concluded that autopsy studies are the gold standard in evaluating the prevalence of MB and that high-resolution CT scanning of coronary arteries should be preferred over coronary angiography studies. It has usually been considered as a benign condition but there are studies suggesting a potential haemodynamic significance of MB and some, usually case reports, indicates a possible association between MB and various cardiac pathologies like AMI, left ventricular rupture, life-threatening arrhythmias, hypertrophic cardiomyopathy, apical ballooning syndrome or sudden death 38 . MB is suggested to be a possible underlying mechanism for MINOCA but a subset of the SMINC-study showed similar prevalence for MB in MINOCA, with or without takotsubo syndrome (TS), as in healthy controls 39 .…”
Section: Myocardial Bridgingmentioning
confidence: 99%
“…Several studies reported that preferential development of atherosclerosis just proximal to bridged segment while the bridged segment itself was free from atherosclerosis. [10][11][12] The reasons for confi nement of atherosclerosis at proximal part of MB while sparing the bridged segment were due to hemodynamic disturbances and signifi cant pressure gradients between the bridged segment and the proximal coronary segment leading to chronic coronary pressure overload with signifi cant endothelial changes. 11 Moreover, the absence of exposure to pericoronary adipose tissue at MB site and increased lymph drainage of the vessel wall, protecting against lipid accumulation within the bridged segment.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The reasons for confi nement of atherosclerosis at proximal part of MB while sparing the bridged segment were due to hemodynamic disturbances and signifi cant pressure gradients between the bridged segment and the proximal coronary segment leading to chronic coronary pressure overload with signifi cant endothelial changes. 11 Moreover, the absence of exposure to pericoronary adipose tissue at MB site and increased lymph drainage of the vessel wall, protecting against lipid accumulation within the bridged segment. 8,11 Elmali et al found that a signifi cant association was observed between the MB depth and systolic narrowing, while there was no signifi cant association between the MB length and systolic narrowing and MB depth was related to patient symptoms of chest pain whereby increased MB depth, but not MB length, causing further may not give the true interaction or relationship between cardiac fat and MB characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, acute myocardial infarction, [24][25][26] ventricular septal rupture, 27 paroxysmal AV block, 28 ventricular tachycardia during exercise 29 or even sudden death 30 had been reported in MB cases. Recently, Hostiuc S et al, 31 performed a meta-analysis of 21 MB studies and found that MB was associated with major adverse cardiac events, OR = 1.52 (95% CI: 1.01-2.30), and myocardial ischemia, OR = 3.00 (95% CI: 1.02-8.82), but not with acute myocardial infarction, cardiovascular death, ischemia (identified using imaging techniques), or positive exercise stress testing. In summary, MB could have significant cardiovascular consequences (MACE, myocardial ischemia) in three ways; 1) by direct systolic compression of the tunneled artery causes delayed relaxation and reduces blood supply, [32][33][34] 2) by induced atherosclerosis of the proximal segment prior to the MB, [35][36][37] as found in this case, and 3) enhanced vasospasm.…”
Section: Role Of Myocardial Bridging In Sudden Deathmentioning
confidence: 99%